2017
DOI: 10.3389/fnana.2017.00009
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Glia in the Peripheral and Central Auditory System Following Noise Overexposure: Contribution of TNF-α and IL-1β to the Pathogenesis of Hearing Loss

Abstract: Repeated noise exposure induces inflammation and cellular adaptations in the peripheral and central auditory system resulting in pathophysiology of hearing loss. In this study, we analyzed the mechanisms by which noise-induced inflammatory-related events in the cochlea activate glial-mediated cellular responses in the cochlear nucleus (CN), the first relay station of the auditory pathway. The auditory function, glial activation, modifications in gene expression and protein levels of inflammatory mediators and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 122 publications
(191 reference statements)
11
77
0
Order By: Relevance
“…It is well known that microglia-macrophages (IBA1-positive cells) are upregulated in response to local cochlear damage induced by ototoxicity or noise exposure. 40,41 For this reason, we analyzed the presence of IBA1-immunopositive cells in ototoxin-damaged animals after engraftment ( Figures 4B-4G). We found that in amikacin-ungrafted control cochlea, a subset of IBA1-immunopositive cells were principally located at the modiolus ( Figure 4E).…”
Section: Human Otic Progenitor Transplantation Triggered An Immune Rementioning
confidence: 99%
“…It is well known that microglia-macrophages (IBA1-positive cells) are upregulated in response to local cochlear damage induced by ototoxicity or noise exposure. 40,41 For this reason, we analyzed the presence of IBA1-immunopositive cells in ototoxin-damaged animals after engraftment ( Figures 4B-4G). We found that in amikacin-ungrafted control cochlea, a subset of IBA1-immunopositive cells were principally located at the modiolus ( Figure 4E).…”
Section: Human Otic Progenitor Transplantation Triggered An Immune Rementioning
confidence: 99%
“…Macrophages have also been detected in the adult cochlea following cochlear insult (Hirose et al, 2005 ; Lang et al, 2006 ; Sato et al, 2010 ; Kaur et al, 2015 ). Damaged SGNs, auditory glial cells and fibrocytes secrete pro-inflammatory signals that promote the infiltration of macrophages (Bas et al, 2015 ; Fuentes-Santamaría et al, 2017 ). Recent studies have shown that immune-related gene expression increases in the developing auditory nerve (Lu et al, 2011 ; Bank et al, 2012 ; Calton et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Microglia upregulation and neural degeneration persisted for up to 9 months following the initial insult. As further evidence for trauma-mediated microglial activation in the cochlea, an increase in Iba1+ cells co-localized with TNF-alpha and IL1-beta has been reported in the spiral ganglion of noise-exposed rats (Fuentes-Santamaria, et al, 2017). These findings support the hypothesis that microglia may be an important source of pro-inflammatory cytokines, such as IL-1beta, IL-6 and TNF-alpha produced in response to noise damage in the cochlea (Fujioka, et al 2006).…”
Section: Discussionmentioning
confidence: 75%
“…Microglia have been described in the context of the brain, spinal cord (Galatro, et al, 2017), and retina (Arroba, et al, 2017), but little is known about the biology of microglial cells in the cochlea of the inner ear, a site vulnerable to damage by aging, noise and ototoxic compounds. Very recent studies have begun to address the role of Iba1+ microglia in response to noise exposure in the peripheral and central auditory system of the rat (Fuentes-Santamaria, et al, 2017), but much more characterization is needed. To address this gap in knowledge, we explored the possibility of harvesting and enriching microglia from the rat cochlea with the goal of immortalizing and cultivating them in culture as a novel microglial cell line.…”
Section: Introductionmentioning
confidence: 99%